Teaching about race and racism in the college classroom : notes from a white professor - Kernahan, Cyndi (Teaching and learning in higher education (West Virginia University Press), 2019)
In this book, Cyndi Kernahan argues that you can be honest and unflinching in your teaching about racism while also providing a compassionate learning environment that allows for mistakes and avoids shaming students. She also differentiates between how White students and students of color are likely to experience the classroom, helping instructors provide a more effective learning experience for all students.